Resolución del caso - Florencio Pablo Segura; María Paz Lucero Zudaire; Roberto Carlos Quiroz; Paul Briggen; Silvana Vanesa Preisz; Joaquín Amadeo Álvarez Castillo (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2024)
-